What would Ben Stein do? : applying the insights of a modern-day pundit to tackle the challenges of business and life - Stein, Benjamin, 1944- (Hoboken, N.J. : John Wiley & Sons, 2011)
'Ben Stein's experience from Washington to Hollywood--and everywhere in between--makes him the ideal individual to offer advice to others. His expertise in countless fields make his valuable, keen observations that cover the range of topics and challenges that most people face every day the perfect topic for his next book, What Would Ben Stein Do? It's a question we'd all be wise to ask ourselves when contemplating an array of issues in both business and life. What Would Ben Stein Do... About a 401(k)? When traveling in a country where he didn't know the language? Performing a job he was rapidly outgrowing? Trapped in a struggling relationship? Negotiating a pay increase? Job hunting in a difficult economy? Delivered with the dry, honest wit that millions of people have come to know and love, Ben Stein's next work What Would Ben Stein Do? will provide advice on any question imaginable - from the man who has all the answers'--
Includes index.
Keywords: Life skills -- Handbooks, manuals, etc; Conduct of life -- Miscellanea